Pendidikan dan Komunikasi Islam dalam Syair 'Aqaid Saeket KHR. Syamsul Arifin dan KHR. As'ad Syamsul Arifin - Anwar, Moch. Nuril; Hadi, Sofyan; Sukarno, Sukarno (Cetta: Jurnal Ilmu Pendidikan, 2024)
This research examines Islamic education and communication contained in the Syair 'Aqaid Saeket by KHR. Syamsul Arifin and KHR. As'ad Syamsul Arifin. This poem was written based on a lecture on the condition of the Madurese people, who are generally laypeople, who have very limited thinking and opportunities for in-depth study or reciting the Koran in Islamic boarding schools and are worried about the influx of deviant religious teachings. The educational method he uses is through the art of composing poetry as an innovative and alternative method. 'Aqaid Saeket is a Madurese term for the term 'Aqaid Khomsin ('Aqaid 50) which is a collection of qualities that are obligatory, muhal and jaiz for Allah SWT and His Messenger. The aim of this research is to reveal the message of Islamic education and communication in the Aqaid Poetry which can be used as an educational example for society. The method used in this research is a qualitative approach with descriptive analysis techniques with specifications for the type of library research (library study). This poem contains Islamic education in three categories, namely the values ​​of faith, worship and morals. Aqidah education, includes belief in Allah with his impossible and improbable obligations, belief in the angels who were sent down, belief in the book, belief in the messengers with their impossible and impossible obligations, belief in the last day, belief in qadla' and qadar. Educational messages about worship, including prayer, zakat, fasting and Hajj. The message of moral education includes morals towards fellow creatures with advice to always be devoted to Allah SWT. The poetry of 'Aqaid Saeket contains five principles of Islamic communication, namely the principle of sincerity, the principle of reward and sin, the principle of positive speech, the principle of supervision, and the principle of mutual influence.